Air Bud spikes back ; Air Bud seventh inning fetch [videorecording (DVD)] - Southon, Mike; Pevec, Katija; Boissonnault, Tyler; McClurg, Edie (Walt Disney Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
Andrea's best friend moves to California. She decides to try and earn enough money for an airplane ticket to visit her friend. But babysitting doesn't pay much, and dogsitting becomes a liability when her charges wreak havoc at the Fernfield summer festival. The boy next door, whose love for volleyball, could be Andrea's ticket to San Diego. In the meantime, Buddy is dognapped and then coerced into nabbing a prized diamond for some bad guys.